Herpes zoster epidemiology in Latin America: A systematic review and meta-analysis - Bardach, Ariel Esteban (2021)
The epidemiology and burden of Herpes Zoster (HZ) are largely unknown, and there are no recent reviews summarizing the available evidence from the Latin America and Caribbean (LAC) region. We conducted a systematic review and meta-analysis to characterize the epidemiology and burden of HZ in LAC. Bibliographic databases and grey literature sources were consulted to find studies published (January 2000 ?February 2020) with epidemiological endpoints: cumulative incidence and incidence density (HZ cases per 100,000 person-years), prevalence, case-fatality rates, HZ mortality, hospitalization rates, and rates of each HZ complication. Twenty-six studies were included with most studies coming from Brazil. No studies reported the incidence of HZ in the general population. In population at higher risk, the cumulative incidence ranged from 318?3,423 cases of HZ per 100,000 persons per year of follow-up. The incidence density was 6.4?36.5 cases per 1,000 person-years. Age was identified as a major risk factor towards HZ incidence which increase significantly in people >50 years of age. Hospitalization rates ranged from 3%?35.7%. The in-hospital HZ mortality rate ranged from 0%?36%. Overall, HZ mortality rates were found to be higher in females across all age groups and countries. The incidence of HZ complications (such as post-herpetic neuralgia, ophthalmic herpes zoster, and Ramsay Hunt syndrome) was higher in the immunosuppressed compared to the immunocompetent population. Acyclovir was the most frequently used therapy. Epidemiological data from Ministry of Health databases (Argentina, Brazil, Colombia, Chile y Mexico) and Institute for Health Metrics and Evaluation?s Global Burden of Disease project reported stable rates of hospitalizations and deaths over the last 10 years. High-risk groups for HZ impose a considerable burden in LAC. They could benefit from directed healthcare initiatives, including adult immunization, to prevent HZ occurrence and its complications.